Pertanggungjawaban Bank serta Perlindungan Hukum Terhadap Nasabah Yang Kehilangan Uang Dalam Bank - Yosaphat Patrick Delano Fernadez; Waiwurin Safrianus; Monika Prisilia Sarah; Stefanus Don Rade (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to study the operational security standards of bank services that can result in losses for customers and bank responsibilities related to customer losses for loss of customer money stored in bank accounts. The method used is a type of normative research using a statutory approach, especially banking regulations. Studies show that a standard bank security system that is less than optimal allows for skimming, phishing, system errors, or human errors that can be detrimental to depositors. Regulatory protection for savers with regard to using their savings in bank accounts can refer to the Consumer Protection Act, BI Regulation No. 16/1/PBI/2014 concerning protection of Consumers of Payment System Services and OJK Regulation number 1/POJK.07/2013 concerning protection of Consumers of the Financial Services Sector, and Article 1365 of the Civil Code. The Bank must be responsible for the deposit customer in the event that the customer's losses are incurred by the Bank. Settlement of customer loss disputes can be reached through two processes, namely the trial mechanism (litigation) and procedures outside the court (non-litigation). Legal protection for bank customers in terms of Law No. 8 of 1999 concerning consumer protection is a guarantee of legal certainty provided by banks to customers because basically this law protects consumers, including customers in general. In accordance with the consumer protection law, banks as business actors are obliged to serve customers correctly and honestly and provide true, clear and honest information regarding the conditions and guarantees of the services provided.